عروض الأطروحات الجامعیة فى دوریات المکتبات والمعلومات العربیة : دراسة تحلیلیة مقارنة - د. محمد رجب وهدان (المجلة الدولية لعلوم المكتبات والمعلومات)
The aim of this study is to analyze the presentations of theses published inthree periodicals from the Arab libraries and information libraries: the ArabLibraries and Information Journals, the recent trends in libraries and information,and Arab studies in libraries and information science. The quantity, quality,language and objectivity of the dissertations presented, the distribution ofdissertations presented in accordance with the approved scientific sections, andthe gap between the time of theses and the publication of their presentations, thebook of presentations of theses and their functions and qualifications, Offerstheses